Ancient Roots of Translation Studies in Uzbekistan: Inquiring into the Contribution of Sogdians to Translation and Cultural Transmission along the Silk Road - Sukhaylbonu Khikmat; Meng Liu (Periodica Journal, 2024)
This article explores the historical foundations of translation studies in Uzbekistan, focusing on the pivotal contributions of the Sogdians and, notably, Sogdian women in fostering linguistic and cultural exchange along the Silk Road. Positioned at the crossroads of the Silk Road, Sogdian merchants and diplomats played crucial roles as mediators between East and West, facilitating the translation of languages as well as religious, scientific, and philosophical concepts. Sogdian women, in particular, had a significant yet often overlooked impact on these processes. Through intercultural marriages and involvement in religious and monastic communities, they aided in translating and adapting texts, especially Buddhist scriptures, thereby promoting the spread of religious and cultural practices across regions. Additionally, the Sogdians expressed creative forms and traditions through their crafts, further enriching cultural exchange. This article delves into the Sogdians' influential role in shaping Central Asia's intellectual, religious, and cultural landscape. Their contributions to translation underscore the significance of intercultural communication in the evolution of early translation practice, offering fresh insights into the role of translation in cultural diplomacy along the Silk Road
Keywords: Translation Studies; Uzbekistan; Sogdians